Developmental trajectories of attachment and depressive symptoms in children and adolescents. Issue 4 (3rd July 2020) - Khan, Faaiza; Fraley, R. Chris; Young, Jami F.; Hankin, Benjamin L.
ABSTRACT: Previous research has found that insecure attachment is associated with depression. In the present study, we use an accelerated longitudinal cohort design to examine how the association between attachment and depression develops during childhood and adolescence. Specifically, 690 children from 3 distinct cohorts (grades 3, 6, and 9) completed self-report measures of attachment and depressive symptoms 3 times over 3 years. Growth curve analyses indicated that attachment anxiety and attachment avoidance were uniquely related to depressive symptoms. Higher levels of attachment anxiety and avoidance predicted higher levels of depressive symptoms over time. Additionally, changes in attachment security were associated with changes in depressive symptoms. The analyses suggest that insecure attachment and depressive symptoms co-vary and that these dynamics are evident in childhood and adolescence.